Perancangan Alat Pengolah Limbah Plastik Jenis PET (Polyethylene Terephthalate) Kapasitas 3 kilogram dengan Menggunakan Kompor Oli Bekas - Lesmana, I Gede Eka; Sihombing, Boyma Fugrystiano; Hartanrie, Rovida Camalia; Tatak K, Arif Riyadi; Aldito, Dias (Jurnal Teknik Mesin, 2025)
Plastic is one of the materials widely used in society, one of which is PET (Polyethylene Terephthalate) plastic. Plastic is basically formed from petroleum, so it can be returned to its original form by the pyrolysis process. The pyrolysis process converts organic material at high temperatures and breaking down into smaller molecular bonds. Research and design of pyrolysis have been extensively studied before, with variations in the types of plastic waste burned or the type of fuel used to achieve the optimal heating rate. The fuel used in previous studies included fuels such as charcoal, LPG gas, and bicket from certain waste. In this study, the combustion process uses a jet stove with used oil fuel so that automotive waste can be used as fuel. The design method used in the manufacture of this plastic waste processing tool is the Pahl & Beitz design method, which begins with identifying problems, developing and planning concepts until the required concept is selected. In this design, the results of the 3 kg capacity pyrolysis design were obtained with the main components, namely a reactor tube with specifications of ?250 mm and a height of 320 mm, a smoke conductor pipe using a galvanized pipe type with ?25.4 mm, a copper spiral condenser pipe with ?1/4 in, a condenser tube with specifications of ?230 mm and a height of 250 mm, a tool frame using 30 mm × 30 mm × 3 mm angle iron made of carbon steel. In testing using Computational Fluid Dynamics simulation in the Solidwork application, a smoke temperature of 400 ? was obtained.